The Effect of Audit Quality and Audit Committee on Financial Reporting Quality: (Empirical Study on Hospitality Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023) - Dhandy Hermawan Madu; Nunung Nuryani; Zaenal Arifin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the effect of audit quality and audit committee on financial reporting quality in hotel sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Based on agency, signaling, and corporate governance theories, this study proposes that higher audit quality and more effective audit committees positively influence the quality of financial reporting. Research Method: This study employed a quantitative approach with descriptive and verificative methods. Secondary data were obtained from audited financial statements and annual reports of 31 hospitality subsector companies listed on the IDX from 2019 to 2023, yielding 155 observations. Audit quality was measured by KAP Big Four reputation, audit opinion, auditor switching, and audit fee disclosure. The audit committee was measured by size, independence, and financial expertise. Financial reporting quality was proxied by absolute discretionary accruals, as measured by the Modified Jones Model. Data were analyzed using multiple linear regression with SPSS version 29. Results and Discussion: The findings show that audit quality partially has a significant positive effect on financial reporting quality, particularly through KAP Big Four reputation and audit opinion. Audit committee characteristics do not individually show significant effects, indicating symbolic compliance rather than substantive oversight. Simultaneously, audit quality and the audit committee significantly affect financial reporting quality. Implications: The findings suggest that companies should strengthen audit committee effectiveness beyond formal structure, while regulators should enhance oversight of audit committee performance. Originality: This study provides empirical evidence from the Indonesian hospitality sector by highlighting the dominance of external audit credibility over internal governance mechanisms in improving financial reporting quality.